Investasi Reksadana Syariah Di Aplikasi Bibit - Karno, Rendi; Martinouva, Rissa Afni (Universitas Islam Negeri Raden Intan Lampung, 2021)
The development of technology is very rapid so that it gives birth to new products that can make it easier for humans to make any transaction easily, the development of interest in conventional and sharia investment in Indonesia is starting to move but lacks experience and knowledge to implement, the seed application takes this opportunity by creating a robo advisor best to answer the problem. There are several kinds of investments contained in the seed application, making it easier for novice investors to make transactions, both conventional and Islamic investments. This study aims to assess the effectiveness and increase the attractiveness of sharia investment enthusiasts in seed applications. Making it easier for sharia investment developers to further develop it in accordance with the provisions of the DSN MUI fatwa no. 20/DSN/MUI/IV/2001.Keyword: Investment, Mutual Funds, Sharia, Bibit